Development of new scaffolds as reversible tissue transglutaminase inhibitors, with improved potency or resistance to glutathione addition12. Issue 2 (12th December 2016) - Apperley, Kim Y. P.; Roy, Isabelle; Saucier, Vincent; Brunet-Filion, Nicholas; Piscopo, Sara-Pier; Pardin, Christophe; De Francesco, Élise; Hao, Catherine; Keillor, Jeffrey W.
Abstract : Starting from known reversible inhibitorCP4d, we have designed two new classes of inhibitors, improving both potency (22b ) and glutathione resistance (27d ). Abstract : Previous studies within our group have yielded a class of cinnamoyl-based competitive reversible inhibitors for tissue transglutaminase (TG2), with K i values as low as 1.0 μM (compoundCP4d ). However, due to the electrophilic nature of their alkene moiety, this class of inhibitors is susceptible to nucleophilic attack by glutathione, a key element in cellular metabolism and toxicity response. To address this issue, we made several modifications to the inhibitor scaffold, ultimately showing that a bis(triazole) scaffold increased resistance to nucleophilic attack, with compound27d being the most potent ( K i = 10 μM). In the process of reducing reactivity, we also prepared a new class of inhibitors, replacing the alkene ofCP4d with an alkyne, leading to a significant increase in potency for compound22b ( K i = 420 nM).